Fetal Dermal Mesenchymal Stem Cell-Derived Exosomes Accelerate Cutaneous Wound Healing by Activating Notch Signaling - Wang, Xiao (Stem Cells Int, 2019)
Fetal dermal mesenchymal stem cells (FDMSCs), isolated from fetal skin, are serving as a novel MSC candidate with great potential in regenerative medicine. More recently, the paracrine actions, especially MSC-derived exosomes, are being focused on the vital role in MSC-based cellular therapy. This study was to evaluate the therapeutic potential of exosomes secreted by FDMSCs in normal wound healing. First, the in vivo study indicated that FDMSC exosomes could accelerate wound closure in a mouse full-thickness skin wound model. Then, we investigated the role of FDMSC-derived exosomes on adult dermal fibroblast (ADFs). The results demonstrated that FDMSC exosomes could induce the proliferation, migration, and secretion of ADFs. We discovered that after treatment of exosomes, the Notch signaling pathway was activated. Then, we found that in FDMSC exosomes, the ligands of the Notch pathway were undetectable expect for Jagged 1, and the results of Jagged 1 mimic by peptide and knockdown by siRNA suggested that Jagged 1 may lead the activation of the Notch signal in ADFs. Collectively, our findings indicated that the FDMSC exosomes may promote wound healing by activating the ADF cell motility and secretion ability via the Notch signaling pathway, providing new aspects for the therapeutic strategy of FDMSC-derived exosomes for the treatment of skin wounds.